A kind of high transparency weather-resistant polyester resin and preparation method thereof

By adjusting the molecular structure of the polyester resin and introducing end hydroxyl prepolymers and modifiers, the limitations of transparent powder coatings in terms of waterproof, corrosion resistance and performance stability are solved, and the transparency and weather resistance are significantly improved, and excellent mechanical properties and leveling are achieved.

CN119371645BActive Publication Date: 2025-03-28ANHUI YONGCHANG NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411976893.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing transparent powder coatings have limitations in waterproofing, corrosion resistance and performance stability, and the high refractive coefficient of polyester resin leads to insufficient transparency. Paints using TGIC as curing accelerator require high glass transition temperature and melt viscosity, which affects leveling and flatness.

Method used

By selecting specific polyols and polyacid monomers, adjusting the molecular structure of the polyester resin, reducing the refractive coefficient, and introducing end-hydroxy prepolymers and modifiers, the cross-linking density, flexibility and adhesion of the coating are improved, thereby improving transparency, weather resistance and mechanical properties.

Benefits of technology

It significantly improves the transparency and weather resistance of transparent powder coatings, enhances the mechanical properties and leveling of the coating, extends service life, and exhibits excellent protection in demanding environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides a high-transparency weather-resistant polyester resin and a preparation method thereof, belonging to the technical field of polymer materials, the preparation method comprising the following steps: adding polyols, dibasic acids and catalysts to a reactor in sequence, heating while stirring, heating at a temperature of 160-180°C for 1-2h, then heating to 235-250°C for insulation reaction for 12-14h, adding an acidolysis agent for reaction for 3-4h, vacuumizing for 1-3h, adding a curing accelerator and an antioxidant, stirring for 20-40min, discharging, cooling, and crushing to obtain the high-transparency weather-resistant polyester resin; wherein the polyol is a mixture of neopentyl glycol, tricyclododecanedimethanol, ethylbutylpropylene glycol and trimethylolpropane. The polyester resin prepared by the present invention is applied to polyester transparent powder coatings, which can significantly improve the transparency and weather resistance of the coating, and has good mechanical properties and leveling properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a high-transparency weather-resistant polyester resin and a preparation method thereof. Background Art

[0002] In recent years, with the continuous improvement of people's environmental awareness, the development of environmentally friendly coatings has received more and more attention. The VOC emissions of transparent powder coatings are almost zero, and the pollution to the environment is greatly reduced. It is one of the ideal environmentally friendly coatings. Especially in the context of the increasing popularity of modern buildings, the requirements for building materials are getting higher and higher. The limitations of traditional transparent powder coatings in terms of waterproofing, corrosion resistance and performance stability are gradually emerging. In order to solve these problems, researchers have begun to develop new anti-corrosion transparent powder coating materials. As a new type of building material, transparent powder coatings have great application prospects in future building materials due to its excellent transparency and aesthetics in living environments.

[0003] Transparent powder coatings mainly include acrylic resin series and polyester resin series. Among them, acrylic transparent powder coatings usually use glycidyl methacrylate type acrylic resin as the base material and dodecanedioic acid (DDA) as a curing accelerator; this type of coating is known for its good coating transparency and weather resistance, but due to its low glass transition temperature and poor storage stability, as well as the problem of low surface tension, the coating film may be prone to surface defects, limiting its wide application. In addition, in order to ensure product quality, acrylic transparent powder coatings need to be produced in a dust-free environment and transported by refrigeration, all of which increase the complexity and cost of production. In contrast, polyester transparent powder coatings use polyester resin as the base material and use triglycidyl isocyanurate (TGIC) or blocked isocyanate as a curing accelerator; this type of coating has good performance in terms of coating hardness, crosslinking density, weather resistance and mechanical strength, and has good compatibility with existing coating varieties, and the raw material and production costs are relatively low, which has a broader market development space. However, polyester resin has a higher refractive index than acrylic resin, which results in insufficient transparency of the transparent powder coating made from it. In addition, polyester transparent powder coating using TGIC as a curing accelerator requires the polyester resin used to have a higher glass transition temperature and melt viscosity. Although these properties help to improve the heat resistance and mechanical strength of the coating, they also have a negative impact on the leveling of the coating, thereby affecting the transparency and flatness of the final coating.

[0004] In order to improve this situation, the prior art adjusts the molecular structure of polyester resin by selecting specific polyol and polyacid monomers to reduce its refractive index; for example, the use of low refractive index polyols such as neopentyl glycol and polyacids such as isophthalic acid can effectively improve the transparency of the coating. The leveling and mechanical properties of the coating can be optimized by precisely controlling the molecular weight and distribution of the polyester resin; a lower molecular weight helps to improve fluidity, while a higher molecular weight can enhance the hardness and weather resistance of the coating. The use of a reasonable molecular weight distribution can make the coating flow better during the curing process and reduce surface defects. The introduction of monomers with special functions, such as monomers containing siloxane groups or fluorides, can improve the weather resistance and UV resistance of polyester resins; by using modified polyols such as polyols containing epoxy groups, additional functional groups can be introduced into the polyester resin to enhance the crosslinking density and chemical resistance of the coating, thereby improving its weather resistance and mechanical properties.

[0005] In general, pure polyester resin series transparent powder coatings are the most applicable and economical ones. Therefore, there is an urgent need for a polyester resin with high transparency and weather resistance. Summary of the invention

[0006] The object of the present invention is to provide a high-transparency weather-resistant polyester resin and a preparation method thereof. The polyester resin has an acid value of 32-37 mg KOH / g, a melt viscosity of 4100-7200 mPa.s at 200° C., and a glass transition temperature of 56-70° C. After being applied to a polyester transparent powder coating, the polyester resin can significantly improve the transparency and weather resistance of the coating, and at the same time has good mechanical properties and leveling properties.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a high-transparency weather-resistant polyester resin, comprising the following raw materials:

[0009] 30-40 parts by weight of polyol, 40-65 parts by weight of dibasic acid, 5-20 parts by weight of acidolysis agent, 0.01-0.8 parts by weight of auxiliary agent.

[0010] Preferably, the polyol is a mixture of one or more of neopentyl glycol, tricyclododecanedimethanol, ethylbutylpropylene glycol, trimethylolpropane, propylene glycol, 2-ethyl-2-butyl-1,3-propanediol, diethylene glycol, hexylene glycol, 1,4-cyclohexanediol, dipropylene glycol, triethylene glycol, and tetraethylene glycol.

[0011] Preferably, the mass ratio of tricyclododecanedimethanol to neopentyl glycol is greater than 2.

[0012] Furthermore, the polyol is a mixture of neopentyl glycol, tricyclododecanedimethanol, ethyl butyl propane and trimethylolpropane.

[0013] Preferably, the amount of tricyclododecanedimethanol used accounts for 14-23wt% of the total amount of raw materials.

[0014] Preferably, the amount of trimethylolpropane used accounts for 0.9-1.4wt% of the total amount of raw materials.

[0015] Preferably, the dibasic acid is one or a mixture of two or more of terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isophthalic acid, adipic acid, and maleic anhydride.

[0016] Furthermore, the dibasic acid is terephthalic acid.

[0017] Preferably, the structural formula of the tricyclododecanedimethanol is a mixture of one or two of the following, and the structural formula is as follows:

[0018]

[0019] Preferably, the acidolysis agent is one or a mixture of two or more of isophthalic acid, adipic acid and trimellitic anhydride.

[0020] Furthermore, the acidolysis agent is isophthalic acid.

[0021] Preferably, the auxiliary agent is a mixture of a catalyst, a curing accelerator and an antioxidant.

[0022] Preferably, a high transparency weather-resistant polyester resin is made from the following raw materials:

[0023] 30-40 parts by weight of polyol, 40-65 parts by weight of dibasic acid, 5-20 parts by weight of acidolysis agent, 0.08-0.12 parts by weight of catalyst, 0.4-0.6 parts by weight of antioxidant, 0.04-0.08 parts by weight of curing accelerator.

[0024] Preferably, the catalyst is one or a mixture of two or more of monobutyltin oxide, dibutyltin chloride, tributyltin chloride, monobutyltin triisooctoate.

[0025] Preferably, the curing accelerator is one or a mixture of two or more of triphenylbutylphosphine bromide, triphenylethylphosphine bromide, triphenylmethylphosphine bromide and triphenylphosphine.

[0026] Preferably, the antioxidant is one of antioxidant 1010, antioxidant 626, antioxidant 168, and antioxidant 1076, or a mixture of two or more thereof.

[0027] The transparent powder coating made of the polyester resin prepared by the preparation method of the present invention has significantly improved weather resistance, and its scratch resistance and wear resistance are significantly improved, thereby increasing the durability of the coating.

[0028] In some embodiments of the present invention, a high-transparency weather-resistant polyester resin comprises the following raw materials:

[0029] 30-40 parts by weight of polyol, 3-5 parts by weight of terminal hydroxyl prepolymer, 1-3 parts by weight of modifier, 40-65 parts by weight of dibasic acid, 5-20 parts by weight of acidolysis agent, and 0.01-0.8 parts by weight of auxiliary agent.

[0030] Preferably, a high transparency weather-resistant polyester resin comprises the following raw materials:

[0031] 30-40 parts by weight of polyol, 3-5 parts by weight of terminal hydroxyl prepolymer, 1-3 parts by weight of modifier, 40-65 parts by weight of dibasic acid, 5-20 parts by weight of acidolysis agent, 0.08-0.12 parts by weight of catalyst, 0.4-0.6 parts by weight of antioxidant, 0.04-0.08 parts by weight of curing accelerator.

[0032] Furthermore, a high-transparency weather-resistant polyester resin comprises the following raw materials:

[0033] 9-11 parts by weight of neopentyl glycol, 15-25 parts by weight of tricyclododecanedimethanol, 3-4 parts by weight of ethyl butyl propanediol, 3-5 parts by weight of terminal hydroxyl prepolymer, 1-3 parts by weight of modifier, 53-56 parts by weight of terephthalic acid, 13-16 parts by weight of isophthalic acid, 1-1.5 parts by weight of trimethylolpropane, 0.08-0.12 parts by weight of catalyst, 0.4-0.6 parts by weight of antioxidant, and 0.04-0.08 parts by weight of curing accelerator.

[0034] In the process of synthesizing polyester resin, the present invention effectively improves the aging resistance and corrosion resistance (salt spray) of the coating by adding a specific terminal hydroxyl prepolymer while ensuring the coating has high transparency, excellent leveling, weather resistance and mechanical properties.

[0035] The hydroxyl-terminated prepolymer significantly improves the aging resistance and corrosion resistance of the transparent powder coating during the polyester resin synthesis process through its unique molecular structure and chemical properties. The hydroxyl group in the hydroxyl-terminated prepolymer can undergo an esterification reaction with the carboxyl group in the polyester synthesis to form a stable ester bond, thereby enhancing the cross-linking density between polymer chains and improving the mechanical strength and density of the coating; this highly cross-linked network structure not only effectively prevents the erosion of the coating by external environmental factors such as moisture, oxygen and ultraviolet rays, prolonging the service life of the coating, but also gives the coating excellent flexibility, making it less likely to crack or peel off when subjected to external forces or temperature changes, further enhancing weather resistance and aging resistance. Among them, the introduction of 2,2-dihydroxymethylbutyric acid provides additional polar groups for the coating. These polar groups can form strong chemical bonds with the surface of the substrate, thereby enhancing the adhesion of the coating. Especially in a salt spray environment, it can effectively prevent the corrosive medium from penetrating into the surface of the substrate, significantly improving the corrosion resistance of the coating. Tris(hydroxymethyl)aminomethane provides more hydroxyl and amino groups, increases the cross-linking points, and further improves the stability and durability of the coating. The intermediate generated by 1,3-bis(aminomethyl)cyclohexane and vinyl ethylene carbonate can introduce carbamate bonds, giving the coating better flexibility and bonding strength, and enhancing the chemical resistance of the coating.

[0036] In summary, the terminal hydroxyl prepolymer improves the aging resistance and corrosion resistance of polyester resin transparent powder coatings by enhancing the crosslinking density, improving flexibility and adhesion, and optimizing the microstructure of the coating, enabling it to exhibit excellent protective performance in harsh environments.

[0037] Preferably, the method for preparing the hydroxyl-terminated prepolymer comprises the following steps:

[0038] Under nitrogen protection, 5-8 parts by weight of vinyl ethylene carbonate are added to a reaction kettle, the temperature is increased, and then 5-8 parts by weight of 1,3-bis(aminomethyl)cyclohexane are added dropwise, and the reaction is continued after the addition is completed to obtain an intermediate; under nitrogen protection, 2-4 parts by weight of 2,2-dihydroxymethylbutyric acid, 1-3 parts by weight of tris(hydroxymethyl)aminomethane and 0.05-0.08 parts by weight of tetrabutyl titanate are added to a reaction kettle, the temperature is increased to react, and then 1-2 parts by weight of 2,2-dihydroxymethylpropionic acid and 1-2 parts by weight of the intermediate are added to continue the reaction to obtain a terminal hydroxyl prepolymer.

[0039] Furthermore, the preparation method of the hydroxyl-terminated prepolymer comprises the following steps:

[0040] Under nitrogen protection, add 5-8 parts by weight of vinyl ethylene carbonate to the reactor, heat it to 110-120°C, then add 5-8 parts by weight of 1,3-bis(aminomethyl)cyclohexane dropwise at a rate of 5-7g / min, and continue to react for 4-6 hours after the addition is complete to obtain an intermediate; under nitrogen protection, add 2-4 parts by weight of 2,2-dihydroxymethylbutyric acid, 1-3 parts by weight of tris(hydroxymethyl)aminomethane and 0.05-0.08 parts by weight of tetrabutyl titanate to the reactor, heat it to 150-170°C to react for 3-5 hours, then add 1-2 parts by weight of 2,2-dihydroxymethylpropionic acid and 1-2 parts by weight of the intermediate and continue to react for 2-4 hours to obtain a terminal hydroxyl prepolymer.

[0041] During the synthesis of polyester resin, modifiers consisting of hydroxyl-terminated hydrogenated 1,3-butadiene homopolymer and hydroxymethyl-terminated polydimethylsiloxane are added to further improve the aging resistance and corrosion resistance of the coating and extend its service life. First, as a soft segment chain, hydroxyl-terminated hydrogenated 1,3-butadiene homopolymer has good hydrophobicity and gas barrier properties, and exhibits more significant hydrolysis resistance and aging resistance than traditional polyether main chains, effectively blocking oxygen, water vapor, water-soluble ions and corrosive gases from entering the coating, thereby protecting it from external environmental factors and extending the service life of the coating. Secondly, the hydroxymethyl-terminated polydimethylsiloxane introduces soft siloxane segments with low surface energy and good hydrophobicity, which can form a dense protective film on the coating surface to reduce the adhesion of harmful substances. The introduction of polysiloxane segments also improves the weather resistance of the coating, enabling it to maintain stable physical properties under harsh environments such as ultraviolet rays, humidity and heat. The flexibility of the polysiloxane segments also helps to alleviate the stress concentration of the coating when it is subjected to external forces or temperature changes, prevent the coating from cracking or peeling, and further enhance the durability of the coating.

[0042] Preferably, the modifier is a mixture of hydroxyl-terminated hydrogenated 1,3-butadiene homopolymer and hydroxymethyl-terminated polydimethylsiloxane in a mass ratio of 1-2:1.

[0043] The present invention also provides a method for preparing a high-transparency weather-resistant polyester resin, comprising the following steps:

[0044] Under nitrogen protection, polyol, terminal hydroxyl prepolymer, modifier, dibasic acid and catalyst are added to the reaction kettle in sequence, and the temperature is gradually increased while stirring, and the temperature is heated at 160-180°C for 1-2 hours, and then the temperature is gradually increased. When the temperature reaches 235-250°C, the reaction is kept warm, and the acid value reaches 5-20 mg KOH / g after the reaction is carried out for 12-14 hours until more than 90wt% of the esterification water is discharged; an acidolysis agent is added, and the reaction is carried out for 3-4 hours, and the acid value reaches 50-70 mg KOH / g; vacuum polycondensation is carried out for 1-3 hours, and the acid value reaches 30-40 mg KOH / g, and the melt viscosity at 200°C is 3500-7500 mPa.s; a curing accelerator and an antioxidant are added, and the mixture is stirred for 20-40 minutes, and the material is discharged, and after cooling and crushing, the preparation method of the high-transparency weather-resistant polyester resin is obtained.

[0045] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0046] 1. The present invention successfully prepares a polyester resin with high transparency, strong weather resistance and excellent mechanical properties by changing the polymer segment structure and reducing the polymer crystallinity. The relative light transmittance of the transparent powder coating made of the polyester resin of the present invention is greater than 98%, and can be used in many aspects, such as furniture decoration, automobile parts, hardware and household appliances, etc.

[0047] 2. Since neopentyl glycol has two symmetrical primary hydroxyl groups and is a structurally symmetrical diol, the synthesized polyester has strong crystallinity and thus low transparency. Based on this, the present invention uses tricyclododecanedimethanol to replace part of neopentyl glycol and other monomers to synthesize resins, and utilizes the rigidity and spatial non-planar structure of alicyclic diols to increase the glass transition temperature of polyester, reduce the crystallization of copolyesters, and thus improve the transparency and weather resistance of polyester. The present invention also adds trimethylolpropane as one of the polyols to further improve the chemical resistance and weather resistance of polyester resins.

[0048] 3. In the process of synthesizing polyester resin, the present invention effectively improves the aging resistance and corrosion resistance of the coating by adding a specific terminal hydroxyl prepolymer, while ensuring that the coating has high transparency, excellent leveling, weather resistance and mechanical properties. The hydroxyl group in the terminal hydroxyl prepolymer can undergo esterification reaction with the carboxyl group in the polyester synthesis to form a stable ester bond, thereby enhancing the cross-linking density between polymer chains and improving the mechanical strength and density of the coating; this highly cross-linked network structure not only effectively prevents the erosion of the coating by external environmental factors such as moisture, oxygen and ultraviolet rays, prolonging the service life of the coating, but also gives the coating excellent flexibility, making it difficult to crack or peel off when subjected to external force or temperature changes, further enhancing the weather resistance and aging resistance of the coating. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] The preparation method of the polyester resin described in the following Examples 1-2 and Comparative Examples 1-6 comprises the following steps:

[0051] Under nitrogen protection, polyols (neopentyl glycol and / or tricyclododecanedimethanol, ethylbutylpropylene glycol and / or trimethylolpropane), dibasic acid (terephthalic acid) and catalyst (monobutyltin oxide) were added to the reaction kettle in sequence, and the temperature was gradually increased while stirring. The mixture was heated at 170°C for 1.5 hours, and then the temperature was gradually increased. When the temperature reached 240°C, the reaction was kept warm. After the reaction was carried out for 13 hours until more than 90 wt% of the esterification water was discharged, the acid value reached 13±7 mg KOH / g; an acidolysis agent (isophthalic acid) was added, and the reaction was carried out for 3.5 hours, and the acid value reached 60±10 mg KOH / g. Vacuum polycondensation was carried out for 2 hours, and the acid value reached 35±5 mg KOH / g. The melt viscosity at 200°C was 5500±2000 mPa.s. A curing accelerator (triphenylethylphosphonium bromide) and an antioxidant (antioxidant 1010) were added, and the mixture was stirred for 30 minutes. min, discharging, cooling and crushing to obtain polyester resin.

[0052] Example 1

[0053] This embodiment provides a high-transparency weather-resistant polyester resin, which is made from the following raw materials:

[0054] 10.4 parts by weight of neopentyl glycol, 24.8 parts by weight of tricyclododecanedimethanol, 3.0 parts by weight of ethyl butyl propane glycol, 54.9 parts by weight of terephthalic acid, 15.0 parts by weight of isophthalic acid, 1.0 parts by weight of trimethylolpropane, 0.1 parts by weight of monobutyl tin oxide, 0.5 parts by weight of antioxidant 1010, and 0.06 parts by weight of triphenylethyl phosphonium bromide.

[0055] Example 2

[0056] This embodiment provides a high-transparency weather-resistant polyester resin, which is made from the following raw materials:

[0057] 9.9 parts by weight of neopentyl glycol, 24.8 parts by weight of tricyclododecanedimethanol, 3.0 parts by weight of ethylbutylpropylene glycol, 54.9 parts by weight of terephthalic acid, 15.0 parts by weight of isophthalic acid, 1.5 parts by weight of trimethylolpropane, 0.1 parts by weight of monobutyltin oxide, 0.5 parts by weight of antioxidant 1010, and 0.06 parts by weight of triphenylethylphosphonium bromide.

[0058] Comparative Example 1

[0059] The difference between this comparative example and Example 1 is that the raw material formula is different, as follows:

[0060] 36.2 parts by weight of neopentyl glycol, 0 parts by weight of tricyclododecanedimethanol, 3.0 parts by weight of ethylbutylpropylene glycol, and 0 parts by weight of trimethylolpropane; other raw materials are the same.

[0061] Comparative Example 2

[0062] The difference between this comparative example and Example 1 is that the raw material formula is different, as follows:

[0063] 21.2 parts by weight of neopentyl glycol, 15.0 parts by weight of tricyclododecanedimethanol, 3.0 parts by weight of ethylbutylpropylene glycol, and 0 parts by weight of trimethylolpropane; other raw materials are the same.

[0064] Comparative Example 3

[0065] The difference between this comparative example and Example 1 is that the raw material formula is different, as follows:

[0066] 11.2 parts by weight of neopentyl glycol, 25.0 parts by weight of tricyclododecanedimethanol, 3.0 parts by weight of ethylbutylpropylene glycol, and 0 parts by weight of trimethylolpropane; other raw materials are the same.

[0067] Comparative Example 4

[0068] The difference between this comparative example and Example 1 is that the raw material formula is different, as follows:

[0069] 1.3 parts by weight of neopentyl glycol, 34.9 parts by weight of tricyclododecanedimethanol, 3.0 parts by weight of ethylbutylpropylene glycol, and 0 parts by weight of trimethylolpropane; other raw materials are the same.

[0070] Comparative Example 5

[0071] The difference between this comparative example and Example 1 is that the raw material formula is different, as follows:

[0072] 10.9 parts by weight of neopentyl glycol, 24.8 parts by weight of tricyclododecanedimethanol, 3.0 parts by weight of ethylbutylpropylene glycol, 0.5 parts by weight of trimethylolpropane; other raw materials are the same.

[0073] Comparative Example 6

[0074] The difference between this comparative example and Example 1 is that the raw material formula is different, as follows:

[0075] 9.4 parts by weight of neopentyl glycol, 24.8 parts by weight of tricyclododecanedimethanol, 3.0 parts by weight of ethylbutylpropylene glycol, and 2.0 parts by weight of trimethylolpropane; other raw materials are the same.

[0076] Performance Test 1

[0077] 1. Acid value test

[0078] Take about 1 g of polyester sample and dissolve it in DMF. After it is completely dissolved, add phenolphthalein and titrate it with KOH solution. The acid value of the polyester sample is calculated by the following formula:

[0079] Acid value = (V × c × 56.11) / m

[0080] Where V is the volume of the KOH solution used, c is the concentration of the KOH solution, 56.11 is the molar mass of KOH (g / mol), and m is the sample mass. For specific test methods, refer to the national standard GB / T 6743-2008.

[0081] 2. Viscosity test

[0082] Use a viscometer to measure the viscosity of the polyester sample, set the temperature to 200°C, and after the temperature stabilizes, take an appropriate amount of the polyester sample, place it in the center of the test bench, and measure the viscosity.

[0083] 3.DSC test

[0084] The polyester sample was tested using a differential scanning calorimeter. 5-10 mg of the polyester sample was weighed and placed on the stage. After setting the parameters in the program, DSC measurement was performed. The measurement temperature range was 25-90°C and the heating rate was 10°C / min.

[0085] Table 1: Basic properties of polyester resin

[0086] Acid value / mg KOH / g Viscosity / mPa.s Glass transition temperature / ℃ Example 1 34 5600 66.8 Example 2 34 6000 67.3 Comparative Example 1 35 5500 62.1 Comparative Example 2 34 5400 63.3 Comparative Example 3 34 5300 63.0 Comparative Example 4 35 5200 60.8 Comparative Example 5 34 5500 65.2 Comparative Example 6 33 5700 66.1

[0087] The polyester resins prepared according to the methods of Examples 1-2 and Comparative Examples 1-6 were respectively applied to transparent powder coatings. The preparation process of the coatings and corresponding coatings is as follows: the polyester resin is uniformly mixed with a curing accelerator TGIC, a leveling agent (GLP503), benzoin and a brightener (SC701) according to the formula ratio in Table 2, and the mixture is tableted, crushed, sieved and electrostatically sprayed through a twin-screw extruder.

[0088] Table 2: Formulation composition of transparent powder coating

[0089] raw material Dosage / g Polyester resin 911.4 Curing accelerator TGIC 68.6 Leveling agent 10 Benzoin 3 Brightener 7

[0090] The coating prepared according to the above method is subjected to performance testing according to national standards or common industry methods, wherein the gloss is measured according to the provisions of GB / T 9754-2007, using an incident angle of 60°; the coating thickness is measured according to GB / T21776-2008; and the impact resistance is measured according to T / GDTL 004-2019 "Green Product Evaluation of Polyester Resins for Weather-Resistant Polyester Powder Coatings". Transparent powder coating transmittance test method: a. Spray the transparent powder coating on a clean and transparent standard glass plate with residual heat, and obtain a transparent coating after curing at 200℃ / 15min. Test the transmittance of the standard glass plate after the sprayed transparent powder coating is cured, that is, the transmittance of the sample after spraying, and compare the transmittance of the standard glass plate after the sprayed transparent powder coating is cured with the transmittance of the pure standard glass plate; the transmittance of the prepared powder coating (excluding the standard glass plate) is recorded as the relative transmittance of the sample, and the relative transmittance of the sample = transmittance of the sample after spraying / transmittance of the standard glass plate × 100%; b. The transmittance of the standard glass plate of the unsprayed sample is: 94.80%.

[0091] Table 3: Basic properties of transparent powder coatings

[0092] Components 60° gloss / ° Coating thickness / um Impact resistance / 50 cm Appearance of coating (visual inspection) Light transmittance of sample after spraying / % Relative light transmittance of sample / % Weather resistance Example 1 121.8 77.0 pass Excellent leveling 93.0 97.9 Excellent Example 2 123.6 78.2 pass Excellent leveling 93.5 98.6 Excellent Comparative Example 1 115.0 75.4 pass Excellent leveling 85.3 89.8 Excellent Comparative Example 2 120.9 76.2 pass Excellent leveling 90.0 94.7 Excellent Comparative Example 3 123.1 78.1 pass Excellent leveling 93.8 98.7 Excellent Comparative Example 4 121.8 76.4 pass Excellent leveling 90.9 95.7 Excellent Comparative Example 5 121.0 77.9 pass Excellent leveling 91.0 95.8 Excellent Comparative Example 6 123.8 75.0 pass Leveling is normal 92.9 97.8 Excellent

[0093] It can be seen from the test results of Tables 1 and 3 that the polyester resin prepared in Example 1-2 is applied to the transparent powder coating formula, which can improve the comprehensive performance of the coating. Comparing Comparative Examples 2-3 with Comparative Examples 1 and 4, it can be seen that the introduction of tricyclododecane dimethanol can significantly improve the transparency of the polyester resin. When the amount of tricyclododecane dimethanol is 15-25 parts by weight (accounting for 14-23wt% of the total amount of raw materials), its comprehensive performance is excellent, and then the amount of tricyclododecane dimethanol is increased, and its performance is almost no longer improved; Comparing Examples 1-2 and Comparative Examples 5-6, it can be seen that when the amount of trimethylolpropane is 1-1.5 parts by weight (accounting for 0.9-1.4wt% of the total amount of raw materials), its comprehensive performance is better than outside this range. Within the formula of this range embodiment, the formula of Example 2 is optimal, with excellent weather resistance and transparency, and good mechanical properties.

[0094] The preparation method of the polyester resin described in the following Example 3 and Comparative Examples 7-10 comprises the following steps:

[0095] Under nitrogen protection, polyols (neopentyl glycol, tricyclododecanedimethanol, ethylbutylpropylene glycol, trimethylolpropane), terminal hydroxyl prepolymer, modifier, dibasic acid (terephthalic acid) and catalyst (monobutyltin oxide) were added to the reactor in sequence, and the temperature was gradually increased while stirring. The mixture was heated at 170°C for 1.5 hours, and then the temperature was gradually increased. When the temperature reached 240°C, the reaction was kept warm. After the reaction was carried out for 13 hours until more than 90 wt% of the esterification water was discharged, the acid value reached 13±7 mg KOH / g; an acidolysis agent (isophthalic acid) was added, and the reaction was carried out for 3.5 hours, and the acid value reached 60±10 mg KOH / g. After vacuum polycondensation for 2 hours, the acid value reached 35±5 mg KOH / g, and the melt viscosity at 200°C was 5500±2000 mPa.s. A curing accelerator (triphenylethylphosphonium bromide) and an antioxidant (antioxidant 1010) were added, and the mixture was stirred for 30 minutes. min, discharging, cooling and crushing to obtain polyester resin.

[0096] Example 3

[0097] This embodiment provides a high-transparency weather-resistant polyester resin, which is made from the following raw materials:

[0098] 9.9 parts by weight of neopentyl glycol, 20.8 parts by weight of tricyclododecanedimethanol, 3.0 parts by weight of ethylbutylpropylene glycol, 4 parts by weight of terminal hydroxyl prepolymer, 2 parts by weight of modifier, 54.9 parts by weight of terephthalic acid, 15 parts by weight of isophthalic acid, 1.5 parts by weight of trimethylolpropane, 0.1 parts by weight of monobutyl tin oxide, 0.5 parts by weight of antioxidant 1010, and 0.06 parts by weight of triphenylethyl phosphine bromide.

[0099] The preparation method of the hydroxyl-terminated prepolymer comprises the following steps:

[0100] Under nitrogen protection, 6.5 parts by weight of vinyl ethylene carbonate were added to the reactor, the temperature was raised to 115°C, and then 6.2 parts by weight of 1,3-bis(aminomethyl)cyclohexane were added dropwise at a dropwise rate of 6 g / min. After the addition was completed, the reaction was continued for 5 hours to obtain an intermediate; under nitrogen protection, 3 parts by weight of 2,2-dihydroxymethylbutyric acid, 2.5 parts by weight of tris(hydroxymethyl)aminomethane and 0.06 parts by weight of tetrabutyl titanate were added to the reactor, the temperature was raised to 160°C and the reaction was carried out for 3.5 hours, and then 1.5 parts by weight of 2,2-dihydroxymethylpropionic acid and 1.5 parts by weight of the intermediate were added and the reaction was continued for 2.5 hours to obtain a terminal hydroxyl prepolymer.

[0101] The modifier is a mixture of hydroxyl-terminated hydrogenated 1,3-butadiene homopolymer and hydroxymethyl-terminated polydimethylsiloxane in a mass ratio of 1.5:1. The hydroxyl-terminated hydrogenated 1,3-butadiene homopolymer has a number average molecular weight of 2000 and the hydroxymethyl-terminated polydimethylsiloxane has a weight average molecular weight of 2200.

[0102] The basic properties of the transparent powder coating corresponding to Example 3 were determined according to the method of the above-mentioned performance test 1; among them, impact resistance / 50cm: passed, coating appearance (visual inspection): excellent leveling, transmittance of the sample after spraying: 94.3%, relative transmittance of the sample: 99.1%, weather resistance: excellent.

[0103] Comparative Example 7

[0104] The difference between this comparative example and Example 3 is that the preparation method of the hydroxyl-terminated prepolymer is different, which is as follows: the preparation method of the hydroxyl-terminated prepolymer comprises the following steps:

[0105] Under nitrogen protection, 3 parts by weight of 2,2-dihydroxymethylbutyric acid, 2.5 parts by weight of tris(hydroxymethyl)aminomethane and 0.06 parts by weight of tetrabutyl titanate were added to the reactor, the temperature was raised to 160°C and the reaction was carried out for 3.5 hours. Then 1.5 parts by weight of 2,2-dihydroxymethylpropionic acid was added and the reaction was continued for 2.5 hours to obtain a terminal hydroxyl prepolymer.

[0106] Comparative Example 8

[0107] The difference between this comparative example and Example 3 is that the preparation method of the hydroxyl-terminated prepolymer is different, which is as follows: the preparation method of the hydroxyl-terminated prepolymer comprises the following steps:

[0108] Under nitrogen protection, 6.5 parts by weight of vinyl ethylene carbonate were added to the reactor, the temperature was raised to 115°C, and then 6.2 parts by weight of 1,3-bis(aminomethyl)cyclohexane were added dropwise at a dropwise rate of 6 g / min. After the addition was completed, the reaction was continued for 5 hours to obtain a terminal hydroxyl prepolymer.

[0109] Comparative Example 9

[0110] The difference between this comparative example and Example 3 is that the modifier is different, specifically as follows: the modifier is a hydroxyl-terminated hydrogenated 1,3-butadiene homopolymer, wherein the hydroxyl-terminated hydrogenated 1,3-butadiene homopolymer has a CAS number of 68954-10-9 and a number average molecular weight of 2000.

[0111] Comparative Example 10

[0112] The difference between this comparative example and Example 3 is that the modifier is different, specifically as follows: the modifier is hydroxymethyl-terminated polydimethylsiloxane, wherein the hydroxymethyl-terminated polydimethylsiloxane has a CAS number of 73138-87-1 and a weight average molecular weight of 2200.

[0113] Performance Test 2

[0114] The polyester resins prepared according to the methods of Examples 2-3 and Comparative Examples 7-10 are respectively applied to transparent powder coatings. The preparation process of the transparent powder coatings and the corresponding coatings is as follows: the polyester resin is uniformly mixed with the curing accelerator TGIC, the leveling agent, the benzoin and the brightener according to the formula ratio in Table 2, and the mixture is tableted, crushed, sieved and electrostatically sprayed by a twin-screw extruder. The coating prepared according to the above method is subjected to performance tests according to national standards or methods commonly used in the industry. Among them, the aging resistance test is tested according to the GB / T1865-2009 standard. The salt spray resistance test is tested according to the GB / 1771-2007 standard, and the sample is placed in a salt spray chamber and the results are observed after 1000 hours.

[0115] Table 4: Aging and corrosion resistance of transparent powder coatings

[0116]

[0117] It can be seen from the above performance test results that the high-transparency weather-resistant polyester resin prepared in Example 3 has excellent aging resistance and corrosion resistance when used for transparent powder coatings. This is because the present invention significantly improves the aging resistance and corrosion resistance of the polyester resin by adopting specific terminal hydroxyl prepolymers and modifiers.

[0118] In comparison, Example 2 and Comparative Examples 7-10 are significantly inferior to Example 3 in the corresponding performance tests because they do not adopt the necessary technical solutions. In Example 2, no terminal hydroxyl prepolymer and modifier are used, and in Comparative Examples 7-8, no terminal hydroxyl prepolymer prepared by a specific method is used. In Comparative Examples 9-10, no specific combination of modifiers is used. It can be seen from the results that this leads to a decrease in the aging resistance and corrosion resistance of the transparent powder coating. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0119] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high transparency weather-resistant polyester resin, characterized in that: Including the following ingredients: 30-40 parts by weight of polyol, 40-65 parts by weight of dibasic acid, 5-20 parts by weight of acidolysis agent, 0.01-0.8 parts by weight of auxiliary agent, 3-5 parts by weight of hydroxyl-terminated prepolymer and 1-3 parts by weight of modifier; The polyol is a mixture of neopentyl glycol, tricyclododecanedimethanol, ethylbutylpropylene glycol and trimethylolpropane; The preparation method of the hydroxyl-terminated prepolymer comprises the following steps: Under nitrogen protection, 5-8 parts by weight of vinyl ethylene carbonate is added to a reaction kettle, the temperature is increased, and then 5-8 parts by weight of 1,3-bis(aminomethyl)cyclohexane is added dropwise, and the reaction is continued after the addition is completed to obtain an intermediate; under nitrogen protection, 2-4 parts by weight of 2,2-dihydroxymethylbutyric acid, 1-3 parts by weight of tris(hydroxymethyl)aminomethane and 0.05-0.08 parts by weight of tetrabutyl titanate are added to a reaction kettle, the temperature is increased to react, and then 1-2 parts by weight of 2,2-dihydroxymethylpropionic acid and 1-2 parts by weight of the intermediate are added to continue the reaction to obtain a hydroxyl-terminated prepolymer; The modifier is a mixture of hydroxyl-terminated hydrogenated 1,3-butadiene homopolymer and hydroxymethyl-terminated polydimethylsiloxane in a mass ratio of 1-2:1; The tricyclododecanedimethanol accounts for 14-23wt% of the total raw material; the trimethylolpropane accounts for 0.9-1.4wt% of the total raw material.

2. The high transparency weather-resistant polyester resin according to claim 1, characterized in that: The preparation method of the hydroxyl-terminated prepolymer comprises the following steps: Under nitrogen protection, add 5-8 parts by weight of vinyl ethylene carbonate to the reactor, heat it to 110-120°C, then add 5-8 parts by weight of 1,3-bis(aminomethyl)cyclohexane dropwise at a rate of 5-7g / min, and continue to react for 4-6 hours after the addition is complete to obtain an intermediate; under nitrogen protection, add 2-4 parts by weight of 2,2-dihydroxymethylbutyric acid, 1-3 parts by weight of tris(hydroxymethyl)aminomethane and 0.05-0.08 parts by weight of tetrabutyl titanate to the reactor, heat it to 150-170°C to react for 3-5 hours, then add 1-2 parts by weight of 2,2-dihydroxymethylpropionic acid and 1-2 parts by weight of the intermediate and continue to react for 2-4 hours to obtain a terminal hydroxyl prepolymer.

3. The high transparency weather-resistant polyester resin according to claim 1, characterized in that: The dibasic acid is one or a mixture of two or more of terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isophthalic acid, adipic acid and maleic anhydride.

4. The high transparency weather-resistant polyester resin according to claim 1, characterized in that: The acidolysis agent is one or a mixture of two or more of isophthalic acid, adipic acid and trimellitic anhydride.

5. The high transparency weather-resistant polyester resin according to claim 1, characterized in that: The auxiliary agent is a mixture of a catalyst, a curing accelerator and an antioxidant; the catalyst is one or a mixture of two or more of monobutyltin oxide, dibutyltin chloride, tributyltin chloride and monobutyltin triisooctanoate; the curing accelerator is one or a mixture of two or more of triphenylbutylphosphine bromide, triphenylethylphosphine bromide, triphenylmethylphosphine bromide and triphenylphosphine.

6. The method for preparing a high-transparency weather-resistant polyester resin according to claim 5, characterized in that: The following steps are involved: Under nitrogen protection, polyol, terminal hydroxyl prepolymer, modifier, dibasic acid and catalyst are added to the reaction kettle in sequence, and the temperature is gradually increased while stirring, and the temperature is heated at 160-180°C for 1-2 hours, and then the temperature is gradually increased. When the temperature reaches 235-250°C, the reaction is kept warm, and the acid value reaches 5-20 mg KOH / g after the reaction is carried out for 12-14 hours until more than 90wt% of the esterification water is discharged; an acidolysis agent is added, and the reaction is carried out for 3-4 hours, and the acid value reaches 50-70 mg KOH / g; vacuum polycondensation is carried out for 1-3 hours, and the acid value reaches 30-40 mg KOH / g, and the melt viscosity at 200°C is 3500-7500 mPa.s; a curing accelerator and an antioxidant are added, and the mixture is stirred for 20-40 minutes, and the material is discharged, and after cooling and crushing, the preparation method of the high-transparency weather-resistant polyester resin is obtained.

Citation Information

Patent Citations

  • Polyester resin and laminate

    JP2022043746A